Eco-Pesantren Management: Harmonizing Islamic Values and Environmental Conservation in Traditional Educational Institutions - Akhmad Saikhu; Akhmad Baiquni; Muhammad Khoirul Lutfi (CV. Bimbingan Belajar Assyfa, 2025)
Environmental degradation and climate change necessitate a shift toward sustainable educational models that integrate moral and spiritual values. This study aims to analyze the implementation of the Eco-Pesantren management model at Pondok Pesantren Mambaul Hikam Jombang as a strategy to harmonize Islamic doctrines with environmental conservation efforts. Using a qualitative case study approach, data were gathered through observations of institutional policies and documentation of participatory environmental activities. The results indicate that the institution successfully integrates